(untitled) (Bangladesh Journal of Medical Science, 2012)
The rare, E.coli strain O104:H4 has been identified as the causative agent of one of the largest ever reported food-borneoutbreaks of gastroenteritis and Hemolytic-uremic syndrome (HUS) in Germany this year. This hypervirulent pathotype possess a unique combination of two pathogens: enterohemorrhagicE.coli (EHEC) and enteroaggregative E.coli (EAEC) strains. The serotype has rarely been described previously in humans and never associated with any earlier large scale EHEC outbreaks. It is now being referred to as the Entero-Aggregative-Haemorrhagic Escherichia coli (EAHEC).Advances in high-throughput sequencing technologies helped in rapid complete genome sequencing of the outbreak strains by different laboratories.Comparison of the genome sequence of the outbreak strain with other diarrhea-associated EAEC serotype O104:H4 indicate that the chromosome of the outbreak strain is most similar to that of an early isolated EAEC strain 55989 and has evolved to become more virulent by the acquisition of a Shiga toxin 2 encoding prophage, a plasmid encoding CTX-M beta-lactamases, and substituting the aggregative adherence fimbria III (AAF/III)with the rarer aggregative adherence fimbria I (AAF/I). The present article reviews the virulent traits ofthe outbreak strain, and also presents an update of the different intervention strategies that are being tested for the treatment of infections by such highly pathogenic strains. DOI: http://dx.doi.org/10.3329/bjms.v11i1.9815 BJMS 2012; 11(1): 4-11